Deformable Polyurethane Joints and Fibre Grids for Resilient Seismic Performance of Reinforced Concrete - Theodoros Rousakis, Alper Ilki, Arkadiusz Kwiecien , Alberto Viskovic , Matija Gams , Petra Triller , Bahman Ghiassi , Andrea Benedetti , Zoran Rakicevic , Camilla Colla , Omer Faruk Halici , Bogusław Zając , Łukasz Hojdys , Piotr Krajewski , Fabio Rizzo , Vachan Vanian, Anastasios Sapalidis , Efthimia Papadouli and Aleksandra Bogdanovic (Polymers, MPDI, 2020)
The behaviour of reinforced concrete frames with masonry wall infills is influenced a lot by the stiffness and strength difference between the frame and the infill, causing early detrimental damage to the infill or to the critical concrete columns. The paper reports the results from shake table seismic tests on a full-scale reinforced concrete (RC) frame building with modified hollow clay block (orthoblock brick) infill walls, within INMASPOL SERA Horizon 2020 project. The building received innovative resilient protection using Polyurethane Flexible Joints (PUFJs) made of polyurethane resin (PU), applied at the frame-infill interface in different schemes. Further, PUs were used for bonding of glass fibre grids to the weak masonry substrate to form Fibre Reinforced Polyurethanes (FRPUs) as an emergency repair intervention. The test results showed enhancement in the in-plane and out-of-plane infill performance under seismic excitations. The results confirmed remarkable delay of significant infill damages at very high RC frame inter-story drifts as a consequence of the use of PUFJs. Further, the PUFJ protection enabled the resilient repair of the infill even after very high inter-story drift of the structure up to 3.7%. The applied glass FRPU system efficiently protected the damaged infills against collapse under out-of-plane excitation while they restored large part of their in-plane stiffness.
Keywords: polyurethane; flexible joint; RC column; brick infill; shake table; resilience